(untitled) (GAIMS Journal of Medical Sciences, 2026)
Background: Medicos must be physically fit before serving patients. Blood pressure and Spirometer variables are essential markers of health status of an individual. . Our study aims at determining the effect of Blood Pressure on Pulmonary parameters of medical students to identify the Risk Groups who are prone to develop Hypertension and to provide recommendations. Material and methods: Students were classified on the basis of BP (viz. Normotensive, Hypertensive). Spirometric variables viz. FVC, FEV1, PEFR of the students were recorded and compared between the hypotensives, normotensives and hypertensive students. The response frequencies and descriptive statistics like mean and standard deviations were calculated. In case of more than two variables, P values were calculated using ANOVA test by Interactive statistics software. The P value <0.05 was considered as significant. Results: Comparison of spirometric variables showed that FVC, FEV1, PEFR values decreased as we go from hypotensives, to normotensives to hypertensives. Conclusion: This study found decreasing trend of pulmonary functions with increase in blood pressure. We recommended for changing life style that includes reduced consumption of fat rich diets, fast foods, salt restriction, performing regular physical exercises, yoga, meditation, sticking to a routine time table for sports, study and sleeping hours so as to tackle the burden of noncommunicable diseases among the new-generation physicians.